Increased Readiness for Adaptation and Faster Alternation Rates Under Binocular Rivalry in Children - Hudak, Mariann; Gervan, Patricia; Friedrich, Bjorn; Pastukhov, Alexander; Braun, Jochen; Kovacs, Ilona (Frontiers in Human Neuroscience, 2011)
Binocular rivalry in childhood has poorly been investigated in the past. Information is scarce with respect to infancy, and there is a complete lack of data on the development of binocular rivalry beyond the first 4-5 years of age. In this study, we are attempting to fill this gap by investigating the developmental trends in binocular rivalry in pre-puberty. We employ a classic behavioral paradigm with orthogonal gratings, and introduce novel statistical measures (after Pastukhov and Braun) to analyze the data. These novel measures provide a sensitive tool to estimate the impact of the history of perceptual alternations on future alternations. We found that the cumulative history of perceptual alternations has an impact on future percepts, and that this impact is significantly stronger and faster in children than in adults. Assessment of the “cumulative history” and its characteristic time-constant helps us to take a look at the adaptive states of the visual system under multi-stable perception, and brings us closer to establishing a possible developmental scenario of binocular rivalry: children adapt faster and stronger, and this increased readiness for adaption seems to be associated with faster alternation rates.